Differential Proteome Analysis of Breast and Thigh Muscles between Korean Native Chickens and Commercial Broilers - De Liu, Xian (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
The Korean native chickens (Woorimotdak™, KNC) and commercial broilers (Ross, CB) show obvious differences in meat flavor after cooking. To understand the contribution of protein and peptide for meat flavor, 2-dimensional (2-D) gel electrophoresis and matrix-assisted laser desorption-ionization time-of-flight (MALDI-TOF) mass spectrometry was performed. A total of 16 protein spots were differentially expressed in the breast and thigh meat between the two breeds. A total of seven protein spots were represented by different levels between KNC and CB for breast meat. Among them three protein spots (TU39149, TU40162 and TU39598) showed increases in their expressions in KNC while other four protein spots (BU40125, BU40119, BU40029 and BU39904) showed increases in CB. All nine protein spots that were represented by different levels between KNC and CB for thigh meat showed increases in their expression in KNC. Phosphoglucomutase 1 (PGM 1), myosin heavy chain (MyHC), heat shock protein B1 (HSP27), cytochrome c reductase (Enzyme Q), Glyoxylase 1, DNA methyltransferase 3B (DNA MTase 3) were identified as the main protein spots by MALDI-TOF mass spectrometry. These results can provide valuable basic information for understanding the molecular mechanism responsible for breed specific differences in meat quality, especially the meat flavour.